Hypothesis: solid tumours behave as systemic metabolic dictators. Issue 6 (4th February 2016) - Lee, Yang‐Ming; Chang, Wei‐Chun; Ma, Wen‐Lung
Abstract: Current knowledge regarding mechanisms of carcinogenesis in human beings centres around the accumulation of genetic instability, amplified cellular signalling, disturbed cellular energy metabolism and microenvironmental regulation governed by complicated cell–cell interactions. In this article, we provide an alternative view of cancer biology. We propose that cancer behaves as a systemic dictator that interacts with tissues throughout the body to control their metabolism and eventually homeostasis. The mechanism of development of this endocrine organ–like tumour (EOLT) tissue might be the driving force for cancer progression. Here, we review the literature that led to the development of this hypothesis. The EOLT phenotype can be defined as a tumour that alters systemic homeostasis. The literature indicates that the EOLT phenotype is present throughout cancer progression. The feedback mechanism that governs the interaction between tumours and various organs is unknown. We believe that investigating the mechanism of EOLT development may advance the current knowledge of regulation within the tumour macroenvironment and consequently lead to new diagnostic methods and therapy.